Microbiology in action - Heritage, J. (Cambridge University Press, 1999)
"Microbes play an important role in our everyday lives. As agents of infectious disease they cause untold human misery, yet their beneficial activities are manifold, ranging from natural cycling of chemical elements through to the production of food, beverages and pharmaceuticals. In this introductory level text the authors provide a clear and accessible account of the interactions between microbes, the environment and other organisms, using examples of both benficial and adverse activities."--Back cover
"Published in association with the Institute of Biology."
Keywords: Microbiology.; Microbiology; Microbiologie.; microbiology.; SCIENCE -- Life Sciences -- Biology.; SCIENCE -- Life Sciences -- Microbiology.; Mikrobiologe; Electronic books.